2009
DOI: 10.1002/maco.200805019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of long‐term corrosion of rebars embedded in concretes sampled on French historical buildings aged from 50 to 80 years

Abstract: International audienceThe aim of this paper is to understand what the chemical influence of the concrete on the corrosion form present is, on rebars embedded for tens or hundreds years. Therefore, metal/concrete interface of samples coming from two French Historical Monuments has been characterized: ‘Bourse du Travail’, Bordeaux, 80 years old and ‘Maison du Brésil de la Cité Internationale de Paris’, 50 years old. The collected samples have been observed on transverse section in order to observe the whole corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 10 publications
6
26
0
Order By: Relevance
“…In good agreement with literature [19] it was found that the corrosion process was often initiated below the reinforcement bar where the ITZ was weakened by sagging of the concrete during the hydration process or large pores originating from air inclusions, see Figure 5b. This phenomenon was also observed by other authors [20][21][22].…”
Section: Macro-cell-corrosion Samplessupporting
confidence: 78%
“…In good agreement with literature [19] it was found that the corrosion process was often initiated below the reinforcement bar where the ITZ was weakened by sagging of the concrete during the hydration process or large pores originating from air inclusions, see Figure 5b. This phenomenon was also observed by other authors [20][21][22].…”
Section: Macro-cell-corrosion Samplessupporting
confidence: 78%
“…9 down) with those observed on some existing concrete structures in France (age between 50 and 80 years). The points labeled BdT, CEA, and MdB are respectively the measured thickness of corrosion products of carbonated samples from Bourse du Travail, water house of CEA and Maison du Brésil structures [4]. We notice that a coefficient k ranging between 1 × 10 −5 and 1 × 10 −6 seems to give more accurate thickness values.…”
Section: Parametermentioning
confidence: 97%
“…Furthermore, since corrosion products have a volume of 3 to 7 times greater than the initial volume of the steel lost (see e.g. [2][3][4]), the corresponding expansion may generate tensile stresses important enough to disrupt the concrete cover and initiate internal cracks that propagate from the steel/concrete interface to the exposed surface. The consecutive physical modifications (related both to mechanical and transport properties) then affect the durability of structure.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term corrosion patterns developed on old steels embedded in cementitious materials [20,21] or exposed to atmospheric conditions [22] are very similar (see Figs. 2 and 3).…”
Section: Long-term Corrosion Patternsmentioning
confidence: 82%